Isolation of TBE virus from the tick Ixodes hexagonus - Krivanec, K; Kopecký, J; Tomková, E; Grubhoffer, L (Folia parasitologica, 1988)
Tick-borne encephalitis (TBE) virus was isolated from a sample of Ixodes hexagonus ticks collected from the hair of the western European hedgehog (Erinaceus europaeus) which had been captured on the edge of a new housing estate in Ceské Budĕjovice at the end of September 1986. This was the first isolation of TBE virus from this vector, supporting the previous experimental results. The virus was identified in immunofluorescent and plaquereduction neutralization tests.
Keywords: viry klíšťové encefalitidy; Neutralization Tests; arachnida jako vektory; myši; Tick Infestations; Fluorescent Antibody Technique; neutralizační testy; Ticks; Arachnid Vectors; zvířata; Mice; Encephalitis Viruses, Tick-Borne; infestace klíšťaty; klíšťata; Hedgehogs; fluorescenční protilátková technika; ježkovití; Animals